Efektivitas Implementasi Standar Audit Intern Pemerintah Indonesia (SAIPI) dalam Mewujudkan Tata Kelola Pemerintahan yang Baik: (Studi Kasus Inspektorat Kabupaten Sidoarjo) - Dyah Anggraini; Ulul Albab; Kristyan Kristyan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research analyses the effectiveness of implementing the Indonesian Government Internal Audit Standards (SAIPI) at the Sidoarjo Regency Inspectorate in achieving good governance. SAIPI constitutes the guidelines established by the Association of Indonesian Government Internal Auditors (AAIPI) through Regulation Number PER-01/AAIPI/DPN/2021 as the minimum quality standard for the execution of government internal audits. The study employs a qualitative approach, utilising data collection techniques via in-depth interviews, observation, and document analysis. The research informants include the Regency Inspector, Assistant Inspectors, senior auditors, and officials from Regional Apparatus Work Units (SKPD) within the Sidoarjo Regency Government environment. The findings indicate that the implementation of SAIPI at the Sidoarjo Regency Inspectorate has been carried out reasonably well, but still encounters several constraints such as limited auditor competency in computer-assisted audit techniques (CAATs), a lack of structural independence, and suboptimal utilisation of information technology in the audit process. Factors supporting implementation include strong leadership commitment, the availability of clear regulations, and continuous auditor capacity-building programmes. The study concludes that the effectiveness of SAIPI implementation positively contributes to the enhancement of internal oversight quality, accountability in regional financial management, and corruption prevention within the Sidoarjo Regency Government.